2013
DOI: 10.1055/s-0033-1333575
|View full text |Cite
|
Sign up to set email alerts
|

Management of Nontuberculous Mycobacterial (NTM) Lung Disease

Abstract: Nontuberculous mycobacterial (NTM) lung diseases present formidable obstacles to successful management, especially when compared with tuberculosis, beginning with diagnosis and extending through treatment. Factors peculiar to NTM disease such as extensive microbial resistance mechanisms and difficult to interpret, even misleading, in vitro drug susceptibility patterns are just two of the multiple and frustrating clinical management challenges. More conventional problems such as drug-drug interactions, medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…CAM resistance has also been reported to be a poor prognostic factor for MAC pulmonary disease. [33] Although recent studies revealed various mechanisms of resistance in NTM, the relationship between in vitro antibiotic susceptibility testing and treatment outcome in a clinical setting has not been established. [34] Since CAM resistance may have been associated with mortality rate in the present study, further investigations, including microbiological studies, are required.…”
Section: Discussionmentioning
confidence: 99%
“…CAM resistance has also been reported to be a poor prognostic factor for MAC pulmonary disease. [33] Although recent studies revealed various mechanisms of resistance in NTM, the relationship between in vitro antibiotic susceptibility testing and treatment outcome in a clinical setting has not been established. [34] Since CAM resistance may have been associated with mortality rate in the present study, further investigations, including microbiological studies, are required.…”
Section: Discussionmentioning
confidence: 99%
“…In deciding antibiotic regimens for pulmonary infections caused by nontuberculous mycobacteria, it is helpful to first divide these organisms into the categories of rapidly growing mycobacteria (RGM) and slow-growing mycobacteria (SGM). Antibiotic regimens for RGM are dictated primarily by the susceptibility patterns of Mycobacterium abscessus and M. fortuitum (10,11). Both M. abscessus and M. fortuitum exhibit inducible macrolide resistance, which is believed to work through activation of the erm gene (12).…”
Section: Paraffinicum Was Initially Isolated From a Soil Sample Inmentioning
confidence: 99%
“…Furthermore, treatment of NTM infections in SOT recipients creates challenges because of drug-drug interactions and overlapping drug toxicities [3], with treatment regimens based on observational data from the non-transplant population [4]. Previous studies of the long-term outcomes of NTM infection among SOT recipients have been limited to lung transplant population [57], with conflicting findings regarding the relationship between NTM infection and mortality.…”
Section: Introductionmentioning
confidence: 99%